Die Wiederherstellung vernünftiger ökonomischer Rahmenbedingungen - Allan H. Meltzer (Kredit und Kapital, 1971)
Restoring a Healthy Economic Environment The fluctuations in economic activities may be explained in two ways. According to the one approach, expansions and contractions of macroeconomic magnitudes are attributable to the inherent instability of the private sector. T'he causes of them are mistakes and erroneous estimates in the combined actions of private individuals and waves of optimism and pessimism based on the long-term anticipations of the business world. It is the task of the government to eliminate instability by means of purposive action. According to this thesis, oniy government activity prevented the collapse of the economy, which was becoming ever more unstable owing to private business policy. The opposite approach regards instability as the delayed effect of former economic policy measures. Theses measures give rise to change anticipation and thus cause the waves of optimism and pessimism. The government, therefore, does not have a stabilizing effect, but contrarily a destabilizing effect on the course of economic activities. Coexistence of the two explanations is quite possible. The evidence of empirical observations, however, is unequivocally in favour of instability being. attributable to inconstancy of the government's economic policy. Monetary policy might be cited as an example of the destabilizing effect. There is no such thing as an inflation which is not characterized by a simultaneous or previous, substantial expansion of the quantity of money. An end to inflation could be achieved gradually by reducing the growth rate of the quantity of money. The cost that has to be borne in so doing is the reduction of output and aggravation of underemployment. The proponents of the first approach and also central bank officials, who incidentally find the thesis of the instability of the private sector very attractive because it enables them to shift their responsibility to others, recommend on the other hand that inflation be combatted with additional government intervention, e.g. wage and price controls, and a general expansion of the government control system to all spheres of the national economy. Each new intervention by the government gives rise to new instabilities. Consequently there is no justification for massive government Intervention; instead a reduction of government activity ıs indicated. For monetary policy that means: complete abstinence from incisive changes; no policy os sharp expansion and then again sharp contraction; rather moderate but continuous growth at a rate of 3 to 4 %.
Keywords: 330